2022
DOI: 10.1016/j.celrep.2022.110399
|View full text |Cite
|
Sign up to set email alerts
|

Follicular T cells optimize the germinal center response to SARS-CoV-2 protein vaccination in mice

Abstract: Follicular helper T (Tfh) cells promote, whereas follicular regulatory T (Tfr) cells restrain, germinal center (GC) reactions. However, the precise roles of these cells in the complex GC reaction remain poorly understood. Here, we perturb Tfh or Tfr cells after SARS-CoV-2 spike protein vaccination in mice. We find Tfh cells promote the frequency and somatic hypermutation (SHM) of Spike-specific GC B cells and regulate clonal diversity. Tfr cells similarly control SHM and clonal diversity in the GC, but do so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 39 publications
(48 reference statements)
1
45
0
Order By: Relevance
“…Moreover, using T FH cell-deletion (T FH -DTR) mice, Cavazzoni et al. showed that reduction of T FH cells results in compromised GC responses and decreased production of anti-S and anti-RBD IgG upon SARS-CoV-2 protein vaccination ( Cavazzoni et al., 2022 ), suggesting that virus-specific T FH cell response is also essential to establish an optimized immune protection in traditional immunization strategy.…”
Section: Virus-specific T Fh Cells In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, using T FH cell-deletion (T FH -DTR) mice, Cavazzoni et al. showed that reduction of T FH cells results in compromised GC responses and decreased production of anti-S and anti-RBD IgG upon SARS-CoV-2 protein vaccination ( Cavazzoni et al., 2022 ), suggesting that virus-specific T FH cell response is also essential to establish an optimized immune protection in traditional immunization strategy.…”
Section: Virus-specific T Fh Cells In Covid-19mentioning
confidence: 99%
“…Evidences of robust responses of SARS-CoV-2-specific T FH cell responses upon administration of mRNA vaccines suggest that virus-specific T FH cell responses contribute to the successful immunization of this preeminent vaccine platform (Painter et al, 2021;Mudd et al, 2022). Moreover, using T FH cell-deletion (T FH -DTR) mice, Cavazzoni et al showed that reduction of T FH cells results in compromised GC responses and decreased production of anti-S and anti-RBD IgG upon SARS-CoV-2 protein vaccination (Cavazzoni et al, 2022), suggesting that virus-specific T FH cell response is also essential to establish an optimized immune protection in traditional immunization strategy.…”
Section: The Functions Of Sars-cov-2-specific T Fh Cellsmentioning
confidence: 99%
“… 36 In an experiment where Tfh cells were perturbed after spike protein vaccination in mice, it was shown that these cells promote the frequency and somatic hypermutation (random mutation of the B-cell receptor/antibody which improves affinity) of germinal center B cells. 37 A study of patients with severe COVID-19 found Tfh-independent antibodies induced by vaccination or infection; while somatic hypermutation was reduced, the antibodies were still of high affinity and durable, and the clonal diversity was actually higher ( Table 1 ). 38 …”
Section: T-cell Control Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Despite lack of GCs, severe COVID‐19 patients still form extrafollicular T–B cell conjugates and class switched antibodies 435,436 . SARS‐CoV‐2 infection and vaccination results in generation of both TFH‐dependent and TFH‐independent antibodies 312,437,438 . Impaired TFH help in immunocompromised kidney transplant recipients likely accounts for decreased responsiveness to mRNA vaccination 439 .…”
Section: Other Forms Of Germinal Center Dysfunctionmentioning
confidence: 99%
“…435,436 SARS-CoV-2 infection and vaccination results in generation of both TFH-dependent and TFH-independent antibodies. 312,437,438 Impaired TFH help in immunocompromised kidney transplant recipients likely accounts for decreased responsiveness to mRNA vaccination. 439 However, Cd4 Cre Bclf6 fl/fl mice demonstrated that although TFHindependent antibodies were less somatically mutated, they were still neutralizing and broadly reactive against SARS-CoV-2 and heterologous viruses.…”
Section: Center Dysfunctionmentioning
confidence: 99%